IMPROVEMENT STRATEGY OF EXPORT PERFORMANCE IN SOUTH SULAWESI - Haris Maupa; Syarifuddin Sulaiman; Hardinasta Perdana (Mega Aktiva, 2019)
The development of new commodities or products that are in line with market needs is a challenge for exporters. The company's export performance reflects the specific behavior of the company in utilizing and managing resources and capabilities effectively in the context of international competition. This study aims to identify what factors influence the increase in export performance of products in South Sulawesi. This study uses a quantitative approach. The method used is indepth interview (in-depth interview), observation and questionnaire. Researchers are required to risk their ability to study more deeply about strategies for improving export performance. Research location in South Sulawesi. The data collected includes primary data and secondary data. The analysis technique in this study is qualitative descriptive, IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) analysis and SWOT (Strengths Weaknesses Opportunities Threats) analysis to design an ideal export performance strategy. The results show that strong internal and external environmental conditions can support the development and improvement of export performance for companies. This finding can contribute to exporters to determine strategic planning in improving their performance.